Análise de propagação de ondas eletromagnéticas na faixa de microondas em ambiente indoor com método 3D FDTD e FDTD 2D modificado - RIBEIRO, Dionisio Raony de Souza (Universidade Federal do Pará, 2017)
This work presents tools of low computing cost and good accuracy to characterize the electromagnetic microwave propagation in indoor environments. It was studied the Finite- Difference Time-Domain (FDTD) method applied to model the propagation in these environments. The study deals with the implementing of a new approach of this method which converses a 3D problem in a 2D one. It is presented a comparative study between the two formulation of the method regarding accuracy, speed and the requirement of computing resources. To apply the 3D formulation, a software was written in FORTRAN with the FDTD 3D parallelized by the MPI library. Then, a cluster with Beowulf architecture was set up run the routine. After the validation of the modified FDTD method, it is applied to characterize an indoor environment regarding its losses. This data was used to obtain the statistical distribution of the parameter n of propagation loss of the environment. The contribution of this work lays on the fact that the researched literature do not present the modified FDTD 2D method applied to indoor environments and the use of simulated data to statistical analysis.